A subsistência das astreintes em caso de improcedência do direito material - Bimonti, Helena (2014)
Without intending to investigate the focus of the doutrine on the nature of the civil law suits, it is possible to consider that they are the method used by the jurisdiction to apply the substantive law in order to solve the conflict of interests. Therefore, its effectiveness has been analyzed in several studies with indisputable legal value, given its importance to the Law. Within this context, and among many legally controversial topics, the present paper intends to do a critical analysis of the effectiveness of the jurisdictional hole, when interpreting the procedural rules aimed to conduct the application of the periodic fine set out in the Code of Civil Procedure, in particular the credit’s holder and the question of its survival in case of rejection of the part’s request (since the lack of norms gives rise to fierce controversy, in doctrine and jurisprudence). Obviously, this paper doesn’t intend to present a panacea for all problems, but just to propose a line of reasonable thought that could help, though humbly, in future decisions, given the lack of the Law